FOSTERING RELIGIOUS TOLERANCE IN THE PERSPECTIVE OF THE QUR'AN - Abdul Haris (SOSIOEDUKASI, 2026)
Religious tolerance has become an increasingly important issue in contemporary pluralistic societies characterized by religious diversity and complex interfaith interactions. This study aims to examine the concept of religious tolerance from the Qur'anic perspective by analyzing its theological foundations, core principles, and historical implementation during the early Islamic period. The study employed a qualitative library research design using a thematic Qur'anic (maudhu'i) approach. Primary data were obtained from relevant Qur'anic verses, while secondary data were collected from classical and contemporary tafsir literature, scholarly books, and academic studies related to religious tolerance in Islam. Data were analyzed through qualitative content analysis to identify major themes concerning freedom of belief, interfaith relations, and social coexistence. The findings reveal that the Qur'an establishes religious tolerance through the principles of non-coercion in religion, recognition of human diversity, respect for religious communities, and encouragement of constructive dialogue and cooperation. Furthermore, historical evidence from the life of Prophet Muhammad and the early Muslim community demonstrates the practical implementation of these principles through the protection of religious freedom and peaceful coexistence with non-Muslim communities. The study concludes that religious tolerance is an integral component of Islamic teachings and offers a relevant ethical framework for promoting social harmony, interfaith understanding, and peaceful coexistence in contemporary multicultural societies.